Why Medical Therapeutic Interventions in Vital Conflict Situations Are Morally Admissible? (Hekima Review, 2016)
This article gives a critical evaluation of the moral admissibility of medical therapeutic interventions in vital conflict situations. A vital conflict situation is present when the life of the mother or the child might be saved if the lives of one or both are in danger. The article argues that medical therapeutic interventions in vital conflict situations – such as ectopic pregnancy and a life threatening pulmonary hypertension – are morally admissible and they are compatible with the Catholic magisterial teaching. This article proposes the principle of double effect that justifies the intervention in vital conflict situations where causing the death of the fetus, albeit foreseen constitutes an indirect and unintended side effect.